Employment effects of the provision of specific professional skills and techniques in Germany - Bernd Fitzenberger; Stefan Speckesser (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2005)
Based on unique administrative data, which has only recently become available, this paper estimates the employment effects of the most important type of public sector sponsored training in Germany, namely the provision of specific professional skills and techniques (SPST). Using the inflows into unemployment for the year 1993, the empirical analysis uses local linear matching based on the estimated propensity score to estimate the average treatment effect on the treated of SPST programs starting during 1 to 6, 7 to 12, and 13 to 24 months of unemployment. The empirical results show a negative lock-in effect for the period right after the beginning of the program and significantly positive treatment effects on employment rates of about 10 percentage points and above a year after the beginning of the program. The general pattern of the estimated treatment effects is quite similar for the three time intervals of elapsed unemployment considered. The positive effects tend to persist almost completely until the end of our evaluation period. The positive effects are stronger in West Germany compared to East Germany.
Keywords: C14; C23; H43; J64; J68; 330; IAB-Beschäftigtenstichprobe; IAB-Leistungsempfängerhistorik; prozessproduzierte Daten; Weiterbildungsförderung - Erfolgskontrolle; Arbeitslosigkeitsdauer; berufliche Reintegration; Arbeitslose; Beschäftigungseffekte; Westdeutschland; Ostdeutschland; Bundesrepublik Deutschland; Arbeitsmarktpolitik; Weiterbildung; Umschulung; Wirtschaftspolitische Wirkungsanalyse; Beschäftigungseffekt; Arbeitslosigkeit; Schätzung; Deutschland